Serum FGF21 levels are associated with brown adipose tissue activity in humans - Hanssen, Mark J.W.; Broeders, Evie; Samms, Ricardo J.; Vosselman, Maarten J.; van der Lans, Anouk A.J.J.; Cheng, Christine C.; Adams, Andrew C.; van Marken Lichtenbelt, Wouter D.; Schrauwen, Patrick (Scientific reports, 2015)
The obesity pandemic has spurred a need for novel therapies to prevent and treat metabolic complications. The recent rediscovery of brown adipose tissue (BAT) in humans made this tissue a possible therapeutic target, due to its potentially substantial contributions to energy homeostasis. Fibroblast growth factor 21 (FGF21) has been identified as a facilitator of cold-induced thermogenesis in humans. Furthermore, pre-clinical studies revealed that FGF21 administration leads to improvement in the metabolic consequences of obesity, such as dyslipidemia and type 2 diabetes. Here we studied plasma FGF21 levels in two cohorts of human subjects, in whom BAT activity was determined using an individualized cooling protocol by [ 18 F]FDG-PET/CT scan. Importantly, we found that circulating FGF21 levels correlated with BAT activity during acute cold exposure in male subjects. In addition, FGF21 levels were related to the change in core temperature upon acute cold exposure, indicating a role for FGF21 in maintaining normothermia, possibly via activation of BAT. Furthermore, cold acclimation increased BAT activity in parallel with increased FGF21 levels. In conclusion, our results demonstrate that FGF21 levels in humans are related to BAT activity, suggesting that FGF21 may represent a novel mechanism via which BAT activity in humans may be enhanced.